The Palgrave Handbook of International Development
XXXIII, 774 p. 15 illus., 9 illus. in color.
Keywords: International development is a dynamic, vibrant and complex field – both in terms of practices and in relation to framing and concepts. This collection draws together leading experts from a range of disciplines, including development economics, geography, sociology, political science and international relations, to explore persistent problems and emergent trends in international development. Building from an introduction to key development theories, this Handbook proceeds to examine key development questions relating to the changing donor and aid landscape, the changing role of citizens and the state in development, the role of new finance flows and privatization in development, the challenges and opportunities of migration and mobility, emerging issues of insecurity and concerns with people trafficking, the drugs trade and gang violence, the role of rights and activism in promoting democracy and development, the threats posed by and responses to global environmental change, and therole of technology and innovation in promoting development. .